MODEL OF WOMEN EMPOWERMENT IN THE FISHERMAN AREA OF BILAH HILIR LABUHANBATU REGENCY - Tengku Irmayani (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
This study aims to describe the model of women's empowerment in fishing areas. This research method uses a qualitative approach. The research was conducted through interviews, field observations, and Focus Group Discussions (FGD) to collect the required data. Informants in this study were representatives from the Department of Marine Affairs and Fisheries and the Office of Cooperatives and Small and Medium Enterprises, as well as women in the fishing area of Bila Hilir. The research location is Bilah Hilir Village, Labuhanbatu Regency, North Sumatra Province which is one of the fishing villages with the community's economic level far below the poverty line. The results showed that low income caused many fishermen's children to drop out of school, and become entangled with moneylenders. The government's lack of attention to developing the fishermen's economy has made women in this fishing area just give up. This study concludes that there has been no empowerment carried out by the Labuhanbatu Regency government for women in the Bila Hilir fishing area.